Provision of social care and social healthcare services in selected municipalities before and after the act on social services took effect - Bareš, Pavel (Univerzita Pardubice, 2010)
The article presents the opinions of the staff of selected municipalities on the provision of social care and social healthcare services. The situation was scrutinised repeatedly, first in 2006 and then in 2008, in the same group of municipalities. That made it possible to identify the situation before and after the entry into effect of Act No. 108/2006, on social services, which introduced a whole series of fundamental changes to the social services.
Keywords: legal regulation; municipalities; social services; medium-term social services development plans